Towards Walkability Transitions in Latin America. Disentangling policy rationalities, institutional path dependencies and technical solutionist projects. - (:unkn) unknown (My University, 2026)
Despite international support for the implementation of urban policies, plans and projects that promote walkability as a mode of transport, there has been limited success, particularly in Latin America. Some explanations highlight the conflicting policy a